2016
DOI: 10.1002/anie.201607445
|View full text |Cite
|
Sign up to set email alerts
|

Solvent‐Driven Reductive Activation of CO2 by Bismuth: Switching from Metalloformate Complexes to Oxalate Products

Abstract: In this work, we investigated how the reductive activation of CO with an atomic bismuth model catalyst changes under aprotic solvation. IR photodissociation spectroscopy of mass-selected [Bi(CO ) ] cluster ions was used to follow the structural evolution of the core ion with increasing cluster size. We interpreted the IR spectra by comparison with density-functional-theory calculations. The results show that CO binds to a bismuth atom in the presence of an excess electron to form a metalloformate ion, BiCOO . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 23 publications
8
70
0
Order By: Relevance
“…formation was found in the reactions with 3‐butyn‐1‐ol as well as with HNO 3. The groups of Weber and Duncan have established a significant amount of data based on the infrared photodissociation spectroscopy of carbon dioxide solvated metal centers M +/− (CO 2 ) n (M=Au, Ag, Co, Ni, Cu, Mg, Fe, Si, V, Al, Bi, TiO), where CO 2 is activated by charge transfer to form the carbon dioxide radical anion CO 2 .− or the oxalate dianion C 2 O 4 2− . Mackenzie et al.…”
Section: Introductionmentioning
confidence: 99%
“…formation was found in the reactions with 3‐butyn‐1‐ol as well as with HNO 3. The groups of Weber and Duncan have established a significant amount of data based on the infrared photodissociation spectroscopy of carbon dioxide solvated metal centers M +/− (CO 2 ) n (M=Au, Ag, Co, Ni, Cu, Mg, Fe, Si, V, Al, Bi, TiO), where CO 2 is activated by charge transfer to form the carbon dioxide radical anion CO 2 .− or the oxalate dianion C 2 O 4 2− . Mackenzie et al.…”
Section: Introductionmentioning
confidence: 99%
“…[29] Cationic metal-CO 2 complexes M + (CO 2 ) n (M = Mg, Al, Si, V, Fe, Co, Ni, Rh, Ir) have been exten-sively investigatedi nt he past decades, [30][31][32][33][34][35][36][37][38][39][40] and also anionic speciesM À (CO 2 ) n (M = Ti,M n, Fe, Co, Ni, Cu, Ag, Au, Sn, Bi) have received considerable attention,f oremost by the group of Weber. [41][42][43][44][45][46][47][48][49][50][51] Generally,t he anionic CO 2 À stretching vibrations shift to the red compared to neutral CO 2 vibrations. [4,52] CO 2 as al igand was also investigated as metal oxides, NbO 2 + (CO 2 ) n and Ta O 2 + (CO 2 ) n by Mackenzie and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt carbonyl cations Co(CO) n + ( n= 1–9) were investigated in an Ar tagging experiment by the group of Duncan, finding one strong absorption for n= 1 at 2156 cm −1 . Cationic metal–CO 2 complexes M + (CO 2 ) n (M=Mg, Al, Si, V, Fe, Co, Ni, Rh, Ir) have been extensively investigated in the past decades, and also anionic species M − (CO 2 ) n (M=Ti, Mn, Fe, Co, Ni, Cu, Ag, Au, Sn, Bi) have received considerable attention, foremost by the group of Weber . Generally, the anionic CO 2 − stretching vibrations shift to the red compared to neutral CO 2 vibrations .…”
Section: Introductionmentioning
confidence: 99%
“…Another assumption is that the weak binding of the tag only subtly affects the inherent absorption spectrum of the ion. In the 2000’s, it was demonstrated that ions could also be cooled and tagged in cryogenic ion traps [911], either with He [12, 13], H 2 [14, 15], D 2 [16, 17], N 2 [18, 19]or Ne [20](so far), and that this approach could then be employed to measure cryogenic IR spectra of ions [12, 18, 2026]. This major advance in principle allows the coupling of any ionization technique with cryogenic spectroscopic interrogation.…”
Section: Introductionmentioning
confidence: 99%